Strategi Guru Dalam Mendisiplinkan Siswa Pada Pembelajaran Tahfizh Quran di SD IT Bayyinah Tahfizhul Qurani - Hamdi Multazam; Ainal Mardhiah; Nurjannah Ismail (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to reveal the strategies employed by teachers in disciplining students during Quranic memorization (tahfizh Quran) learning at SDIT Bayyinah Tahfizhul Qurani. A qualitative research method with a case study approach was utilized in this study. Data were collected through classroom observations, interviews with teachers, and analysis of curriculum-related documents and learning activities. The results of the research indicate that teachers utilize several effective strategies in disciplining students, including the implementation of clear rules, character building through religious education, consistent reward and punishment, and involvement of parents in the learning process. The implications of this research underscore the importance of teachers' role in creating a learning environment conducive to student discipline in Quranic memorization.